STAGES OF FORMATION OF THE INNOVATION-ORIENTED PERSONALITY OF THE FUTURE TEACHER OF PHYSICAL EDUCATION - Дмитрієва, Ніколь (SWorldJournal, 2024)
The purpose of the article is to reveal the essence of the stages of formation of the innovation-oriented personality of the future teacher of physical education. During the study, the stages of implementation of pedagogical support for the formation of a